Approach Paper, Country Program Evaluation - Papua New Guinea : An Evaluation of World Bank Support FY08-22 - Independent Evaluation Group (World Bank,Washington, DC, 2022)
This Country Program Evaluation (CPE) will assess the World Bank Group’s engagement in Papua New Guinea between FY08 and FY22. The Papua New Guinea has an abundant resource endowment of oil and mineral wealth, but this wealth has not translated into significant welfare gains for most citizens. Papua New Guinea’s fragmented geography and frequent exposure to disasters caused by natural hazards present significant challenges for delivering services to citizens. The evaluation is designed to derive lessons from Bank Group engagement in Papua New Guinea to inform the next Country Partnership Framework (CPF). The CPE will also provide lessons on the implementation of the International Development Association special themes of climate change, gender, and fragility, conflict, and violence and of the cross-cutting issues of debt sustainability and governance and institutions. Lessons may also be of relevance to other resource-rich countries.